(untitled) (International Journal of Engineering and Computer Science, 2017)
Android mobile apps is used to provide information regarding there college .Android is the fastest growing open source mobile device platform, which in turn is powered by Linux operating system. Android offers a simple yet powerful application development framework (C++/Java and XML) and open access to APIs to build richer mobile applications. Android is a software stack for mobile devices that includes an operating system, middleware and key applications. Today in colleges student details are entered manually. The student separate records are tedious task. Referring to all these records and updating is needed. There is a chance for more manual errors. As mobile devices have become popular; there appears a new trend to release all kinds of campus information by intelligent mobile terminals. We describe a network for distributing campus information among lecturers and students. The concept of developing campus information system is to ensure that student can access information at any time, at any locations and ad-hoc basic. Information System helps the students and lecturers on campus to find and access information based on ad-hoc basic, which is of interest and relevant to students or lecturers through a smart phone.